Ecological efficiency and thermoeconomic analysis of a cogeneration system at a hospital - Silveira, Jose Luz [UNESP]; Lamas, Wendell de Queiroz [UNESP]; Tuna, Celso Eduardo [UNESP]; de Castro Villela, Iraides Aparecida; Miro, Laura Siso (Pergamon-Elsevier B.V. Ltd, 2012)
This work aims with an approach for cogeneration plants evaluation based on thermoeconomic functional diagram analysis. The second law of thermodynamics is used to develop a methodology to analyse cogeneration systems, based on exergoeconomics evaluation. The thermoeconomic optimisation method developed is applied to allow a better configuration of the cogeneration plant associated to a university hospital. Also ecological efficiency is evaluated. The method was efficient and contributes for thermoeconomics modelling and analysis and can be applied to any sort of thermal system, especially those with combined heat and power in thermal parity. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Ecological efficiency; Exergetic production cost (EPC); Exergy; Functional analysis; Thermoeconomic functional diagram